Quality control using the failure mode effect and analysis to reduce defects in PT. NSP - Nova Wisnianingsih; Agus Nurrokhman (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
This research is to analyze service quality and customer satisfaction to find out the factors of consumer/customer complaints so that company performance can be improved and improved. This research uses the Servqual method, the company can then find out consumers' perceptions and expectations, while the company's AHP method is able to sort out which criteria are prioritized first to improve service quality so that the hospital becomes better. The results of the research were conducted with a sample of 100 respondents and 20 question items. In calculating the weighted servqual, the priority for improving the quality of service in the Tangiable dimension is the criterion "The company has a clean, comfortable waiting room and air conditioning" with a weighted servqual value of -0.020, Reliability is the criterion "doctor's availability according to schedule" with a weighted servqual value of -0.058 , Responsiveness is the criterion of "officer's thoroughness in providing services" with a weighted servqual value of -0.074, Assurance is the criterion of "guaranteeing timeliness of service" with a weighted servqual value of -0.096, Emphaty is the criterion of "officer's sincerity in handling consumers" with a weighted Servqual value of -0.072. The most satisfactory criterion is the Reliability dimension which has the criteria "fast and uncomplicated service procedures" with a weighted servqual value of -0.010.